(untitled) (Gaceta de Ciencias Veterinarias, 2018)
Toxocara spp. are intestinal helminths frequently found in dogs and cats and are capable of causing a parasitic zoonotic disease called toxocariosis. Feces from infected animals represent the main source of environmental contamination and humans can become infected through the accidental ingestion of larval eggs of Toxocara spp. present in soil of public parks, gardens and homes courtyards. These eggs can remain viable in environment for 2 to 4 years or more, being a latent risk factor for human. The research objective was to determine presence of eggs of Toxocara spp. on the houses courtyards and feces of pet dogs of the city of Barquisimeto, Lara State, Venezuela. Samples were taken from soil of previously selected houses courtyards according to established inclusion criteria and analyzed by applying the modified Sloss technique. Feces samples were taken from pet dogs present in these homes and analyzed using the Willis technique. For calculations, frequency and percentage tables were used as well as the association tests: Chi square and Fisher exact test with the statistical package SPSS 15.0 for Windows and 95% was considered as an statistical reliability index (P <0.05). Toxocara spp. eggs were found in 34.28% of houses studied yards and in 15% of the dog population. No association was found between presence of Toxocara spp. eggs on the feces of pet dogs and parasitic contamination on houses courtyards soil. The contact of people with these places represents an important risk factor to consider in transmission of toxocariosis to humans.